The Bacterial Microbiome of the Tomato Fruit Is Highly Dependent on the Cultivation Approach and Correlates With Flavor Chemistry - Escobar Rodríguez, Carolina; Novak, Johannes; Buchholz, Franziska; Uetz, Pia; Bragagna, Laura; Gumze, Marija; Antonielli, Livio; Mitter, Birgit (Frontiers in Plant Science, 2021)
The tomato (Solanum lycopersicum L.) is the highest-value-fruit and vegetable crop worldwide and an important source of micronutrients in the human diet. Flavor is a critical quality characteristic for the acceptance of fresh tomatoes by the consumer. Nonetheless, modern commercial tomato varieties have become substantially less flavorful as a result of breeding and cultivation practices that aim to increase yield and disease resistance. In this work, tomato plants of five different varieties were grown in soil and hydroponically to investigate the impact of the cultivation method in the flavor of fruits, and to assess whether variations in their organoleptic properties are attributable to shifts in bacterial microbiota. Ripe fruits were harvested and used for bacterial community analysis for the analysis of tomato aroma components, and flavor compounds. Fruits grown in soil showed significantly higher sugar contents, whereas tomatoes from plants under hydroponic conditions had significantly higher levels of organic acids. In contrast, aroma profiles of fruits were shaped by the tomato variety, rather than the cultivation method. In terms of bacterial communities, the cultivation method significantly defined the community composition in all cultivars, with the bacterial communities in hydroponic tomatoes being more variable that those in tomatoes grown in soil. Bacterial indicator species in soil-grown tomatoes correlated with higher concentrations of volatiles described to be perceived as “green” or “pungent”. A soil-grown specific rASV classified as Bacillus detected solely in ‘Solarino’ tomatoes, which were the sweetest among all varieties, correlated with the amounts of aroma-relevant volatiles as well as of fructose and glucose in the fruits. In contrast, indicator bacterial species in hydroponic-derived tomatoes correlated with the amounts of aroma compounds with “sweet” and “floral” notes and showed negative correlation with glucose concentrations in fruits. Overall, our results point towards a microbiota-related accumulation of flavor and aroma compounds in tomato fruits, which is strongly dependent on the cultivation substrate and approach.